The Effect Of Education Through Leaflet Media On The Level Of Knowledge And Attitudes Of Mothers Regarding Stunting In The Working Area Of The Cot Seumeureung Puskesmas, Samatiga Sub-District - Damayanti, Siti; Rahmadaningsih, Dinda; Apriani, Fitri; Nasution, Nurromsyah; Syawali, M. (Institute Of Computer Science (IOCS), 2025)
Stunting is a condition of impaired growth in children under five years old, characterized by aheight or length below minus two standard deviations for children of the same, age. Objective : This studyaimed to examine the effect of leaflet media on mothers’ knowledge and attitudes regarding stunting in Cot Seumereung Healt Center, Samatiga. This study used a one-group pretest-posttest experimental design approach. 35 mothers with children under five were selected as the sampel throught total sampling. Results : Before the leaflet based education on stunting, the level of mothers’ knowledge and attitudes was categorized as good in 4 respondents (14.4%). Adequate in 6 respondents (17,1%). And poor in 25 respondents (71.4%). After the implementation, the results improved, with 24 respondents (68.6%) in the good category and 11 respondents (31.4%) in the adequate category. The Wilcoxon test showed a significant result, with Asymp. Sig. (2-tailed) at 0.000. since the p-value of 0.000 is less than 0.05, and the Z value obtained is -5.6015b, these findings indicate a significant effect of leaflet-based education on mothers’ knowledge an attitudes toward stunting. There is a notable impact of leaflet media education on mothers’knowledge and attitudes regarding stunting. The findings of this study are expected to inform and support improvements in mothers’ knowledge and attitudes about stunting. The Cot Seumeureung Health Center in encouraged to promotr educational initiatives on stunting through leaflet presentations to enhance awareness and attitudes among mothers